Analisis Nilai Sosial dalam Cerita Rakyat Sendang Sani di Pati - Zerra Putri Angelina; Diah Ayu Anisa Putri; Arzella Devi Ristia Putri; Shinta Aninda Pratiwi; Nuzulun Niswah; Mohammad Kanzunnudin (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to analyze the social values in the folklore of Sendang Sani in Pati. The story of Sendang Sani, contained in the book Folklore of the East Coast by Mohammad Kanzunnudin, was published by CV Adhigama in 2024. The story appears on page 129 of the total 230 pages of the book measuring 15.5 × 23 cm. The story contains various social values such as devotion, helping, kinship, care, discipline, empathy, justice, tolerance, and cooperation. These values are reflected by the characters, especially Sunan Bonang, Ki Ahmad, and Ki Dudho. This research used descriptive qualitative approach with literature study method and data analysis technique of Miles and Huberman model. The results showed that the Sendang Sani story has great potential as a medium for local culture-based character learning. Therefore, the integration of local folklore in the educational curriculum is necessary for cultural preservation and strengthening the character of the younger generation.